DENIAL OF NОSTALGIA: DESTILLUSION OF HOMELAND IN MIRKO DEMIC'S POSTWAR PENTALOGY - Vladimir Perić (Philological Studies, 2020)
Mirko Demić’s war pentalogy provides a complex and nuanced view of nostalgia as part of the epistemological world. The exile’s sorrow for a lost country is shown through the instability of the émigré’s post-war identity, the traumas caused by the 1990s wars on the territory of former Yugoslavia and the essential impossibility of a return. An unstable self contains emotional cracks that arise from the lack of homeland, the (self)naming of the refugee and his (self-)marginalization, reaching a climax in the narrator’s silence. The devastating effect of war is evident in the meticulously depicted entropy of a warrior’s psyche, a re-examination of desertion, a sense of superfluousness in the mad military carnival. A special narrative obsession with (Balkan) borders places the protagonists of Demić’s stories and novels in borderline situations. The national boundaries, the cross-border “walls”, essentially hinder the return of the expatriate, and his longing for the things he left behind intensifies.The wounded self attempts to achieve a measure of psychological equilibrium by opening the question of forgetting. Another important point is the narrator’s need to overcome the victim experience and his witnessing of violence, and to deal with nostalgia by rationalizing it, by suppressing the binary opposition of the place one longs for and the place one inhabits. The writer finds the means to abolish the stasis of homeland loss: in creating a superborder, a superstructure, a mythical parergon, a parable of Odysseus’s homecoming and a temporal escapism. In it, the literary topos of his homeland, Petrova Gora, is positioned in an ancient historical framework, suitable for the interpretation of agon, both within man and between warring nations.